2021
DOI: 10.3390/ijms22041587
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Controls Nutrient Availability in Hypothalamic Astrocytes

Abstract: Adiponectin, an adipose tissue-derived hormone, plays integral roles in lipid and glucose metabolism in peripheral tissues, such as the skeletal muscle, adipose tissue, and liver. Moreover, it has also been shown to have an impact on metabolic processes in the central nervous system. Astrocytes comprise the most abundant cell type in the central nervous system and actively participate in metabolic processes between blood vessels and neurons. However, the ability of adiponectin to control nutrient metabolism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It should be mentioned here that there is inconsistent data regarding HMGCS2 expression in the nervous tissue. While some authors showed a lack of expression of HMGCS2 in astrocytes and neurons ( Thevenet et al, 2016 ), the latest studies confirm the astrocytic expression of HMGCS mRNA ( Song et al, 2021 ). HMGCS has been found to be abundantly expressed in the astrocytes of the optic nerve ( Metwally et al, 2019 ) and other glial cells ( Wang et al, 2016 ) and various brain areas ( Shao et al, 2019 ; Kondo et al, 2020 ), including the hippocampus ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned here that there is inconsistent data regarding HMGCS2 expression in the nervous tissue. While some authors showed a lack of expression of HMGCS2 in astrocytes and neurons ( Thevenet et al, 2016 ), the latest studies confirm the astrocytic expression of HMGCS mRNA ( Song et al, 2021 ). HMGCS has been found to be abundantly expressed in the astrocytes of the optic nerve ( Metwally et al, 2019 ) and other glial cells ( Wang et al, 2016 ) and various brain areas ( Shao et al, 2019 ; Kondo et al, 2020 ), including the hippocampus ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the physical transportation and biochemical processes of fuel sources in the vessel–astrocyte-neurons axis of the hypothalamus are important in the hypothalamic circuit regulating whole-body energy metabolism. Considerable effort has been made to unveil the functional role of hypothalamic astrocytes in the hypothalamic control of energy metabolism [ 6 , 7 , 10 , 11 , 23 , 24 ]. For instance, the modification of glucose and fatty acid availability in hypothalamic astrocytes altered the susceptibility to obesity development in association with altered activities of hunger- and satiety-regulating neurons in the hypothalamic arcuate nucleus [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample was transferred into auto-sampler vials and analyzed by gas chromatography-mass spectrometry (GC-MS, a GCMS-QP2010 Ultra system, Shimadzu, Kyoto, Japan). GC-MS analysis was performed as previously described (Song et al 2021 ). Pearson's correlation analysis was carried out using SAS software 9.4 (SAS Institute, San Diego, CA, USA) and then visualized with Hierarchical Clustering Analysis (HCA) using Multi-Experiment Viewer version 4.9.0 (MeV; https://webmev.tm4.org ).…”
Section: Methodsmentioning
confidence: 99%